ORGANIZING OF MEASURES FOR PREVENTING THE DELIVERY AND SPREADING OF SEVERE ACUTE RESPIRATORY SYNDROME AT THE TERRITORY OF YAKUTIA - A. P. Protodyakonov (Scientific Сentre for Family Health and Human Reproduction Problems, 2020)
Materials concerning the sanitary protection of the territory of Sakha (Yakutia) from «atypical pneumonia» (SARS) delivery during the epidemic complication in the world are presented in the article. The activity of the region on preventing of SARS delivery by taking of legal and normative documents is shown. Mobilization capacity of the organs and institutions for expanding the measures in case of SARS delivery is reflected, the algorithm of operations is developed.